EP1345 Pelvic lymphadenectomy: step-by-step surgical education video. (1st November 2019) - Selcuk, I; Uzuner, B; Boduc, E; Baykus, Y; Akar, B; Gungor, T
Abstract : Introduction/Background: Pelvic lymphadenectomy is a supplementary part of staging and treatment in gynecologic oncology. Methodology: This video demonstrates a right side systematic pelvic lymphadenectomy in a cadaveric model with proper anatomic landmarks. Results: The borders of pelvic lymph nodes are genitofemoral nerve laterally, bifurcation of common iliac artery cranially, deep circumflex iliac vein caudally, obturator nerve inferiorly and obliterated umbilical artery medially The fibroadipose lymphatic tissue over the external iliac artery is gently elevated and mobilized medially, a tiny dissection is applied to separate the lymphatic tissue from the fibrous sheath. While dissection is carried out longitudinally over the external iliac artery; at the mid-level a cleavage is opened to clear the lymphatic tissue over the external iliac vein until the level of deep circumflex iliac vein whichis the caudal border. Therefore, internal iliaclymph nodes are also removed over the anterior part of internal iliac artery. Afterwards, lymph node dissection turns around the superior pubic ramus of pubic bone which forms a part of obturator foramen and pubic vein the connection between the external iliac and obturator vein (corona mortis) is identified. By the way, dissection of obturator lymph nodes starts from this point after retraction of external iliac vessels laterally to the psoas muscle and maintaining a medial retraction on the paravesical space (that retracts the obliterated umbilical artery medially). All the lymphatic tissue over the obturator nerve medial to the obliterated umbilical artery is stripped from the attachments and finally the lymphatic tissue is removed. Conclusion: Learning the proper technique of pelvic lymphadenectomy with anatomical landmarks will improve the surgical skills and confidence. Disclosure: Nothing to disclose